2010
DOI: 10.1002/ajp.20895
|View full text |Cite
|
Sign up to set email alerts
|

Population‐level right‐handedness for a coordinated bimanual task in naturalistic housed chimpanzees: replication and extension in 114 animals from Zambia and Spain

Abstract: Recently, many studies have been conducted on manual laterality in chimpanzees. Nevertheless, whether nonhuman primates exhibit population-level handedness remains a topic of considerable debate. One of the behaviors studied has been bimanual coordinated actions. Although recent studies have highlighted that captive chimpanzees show handedness at population level for these tasks, some authors have questioned the validity and consistency of these results. The first reason has been the humanization of the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
84
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 65 publications
(93 reference statements)
5
84
1
Order By: Relevance
“…Unlike spider monkeys, capuchins have been characterized as highly dexterous. In studies of Old World monkeys and chimpanzees that have reported digit use, D2 was also the preferred digit [ Table I; Hopkins, 1995;Llorente et al, 2009Llorente et al, , 2011. By comparison, D2 was preferred in 7 of the 9 spider monkeys in this study (all right-handers and two-thirds of left-handers).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Unlike spider monkeys, capuchins have been characterized as highly dexterous. In studies of Old World monkeys and chimpanzees that have reported digit use, D2 was also the preferred digit [ Table I; Hopkins, 1995;Llorente et al, 2009Llorente et al, , 2011. By comparison, D2 was preferred in 7 of the 9 spider monkeys in this study (all right-handers and two-thirds of left-handers).…”
Section: Discussionmentioning
confidence: 47%
“…The coordinated bimanual TUBE task is an example of a measure that constrains hand use by requiring the subject to Conflicts of interest: None. hold a tube with one hand and extract adhesive food from inside the tube with the opposite hand. First introduced by Hopkins [1995] in chimpanzees (Pan troglodytes), the TUBE task has been widely used in all of the great apes [Bardo et al, 2015;Begg-Reid & Schillaci, 2008;Chapelain et al, 2011;Chapelain & Hogervorst, 2009;Hopkins, 1999a;Hopkins et al, 2001Hopkins et al, , 2003Hopkins et al, , 2011Llorente et al, 2009Llorente et al, , 2011, as well as many monkey species (Table I). Findings from the TUBE task have varied across species, although there is some evidence supporting a pattern of left bias in arboreal species and a right bias in terrestrial species [Meguerditchian et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated a close resemblance between some handedness patterns in great apes and humans [1][2][3]. Despite this, comparative systematic investigations of manual lateralization in non-primate mammals are very limited [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral asymmetries in the upper limbs of great apes are, however, less well documented, even though these are potentially informative about the origins of functional lateralization in humans and non-human primates. Indeed, the question of whether non-human primates exhibit individual or population-level functional laterality remains unclear and controversial: behavioural studies, for example, suggest that handedness in great apes can in some instances reach exclusive use of one arm (e.g., right arm [Humle and Matsuzawa, 2009;Meguerditchian et al, 2010;Llorente et al, 2011]; left arm [Parnell, 2001;Lonsdorf and Hopkins, 2005]), but this pattern seems to be strongly dependent on factors such as age, sex, task complexity, setting and posture [Byrne and Byrne, 1991;McGrew and Marchant, 1997;Byrne, 2004;Hopkins and Cantalupo, 2005;Lonsdorf and Hopkins, 2005;Marchant and McGrew, 2007;Pouydebat et al, 2010;Hopkins et al, 2011], and overall, these species do not exhibit the overwhelming right-hand bias across a wide range of everyday tasks so evident in humans Marchant 1997, 2001;Cashmore et al, 2008].…”
Section: Introductionmentioning
confidence: 99%